A PBT fiber with stable melt viscosity and low breakage rate and preparation method thereof
By refining and preciselying the PBT production process and controlling the melt viscosity, the problem of high breaking rate caused by instability in the preparation of PBT fibers is solved, and the goals of low breaking rate and high fiber quality are achieved.
Patent Information
- Application Number
- CN202410474093.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-19
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-04-19
AI Technical Summary
In the prior art, the unstable melt viscosity during the preparation of PBT fibers leads to a high breaking rate, resulting in product loss and fiber quality reduction.
By refining and preciselying the industrial production process of PBT, controlling the process parameters at different production stages, a polyester material with stable and controllable melt viscosity is produced, and PBT fibers are directly produced using spinning technology.
It effectively reduces the breaking phenomenon caused by unstable melt viscosity during fiber manufacturing, reduces product losses, and improves fiber quality.
Smart Images

Figure CN118326546B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester fiber preparation, in particular to a PBT fiber with controllable melt viscosity and low breakage rate and a preparation method thereof. Background Art
[0002] At present, polyester materials such as polyethylene terephthalate (PET), polytrimethylene terephthalate (PTT), and polybutylene terephthalate (PBT) are prepared into polyester long fibers or short fibers through processes such as spinning and cooling, and then applied to the fields of clothing products, bedding, and decorative fabrics, which has become an important part of the textile industry. However, in the process of preparing fibers, polyester materials in the prior art are prone to breakage caused by melt viscosity fluctuations, which also causes huge product losses and fiber quality degradation. Based on this, the current solution is usually to transform the equipment, or to detect the polyester melt viscosity in real time, and to optimize the viscosity of different products using chain extenders to reduce the breakage rate (CN116607244).
[0003] At present, the industrial production route of PBT usually adopts a three-step method (CN106220836), which includes an esterification process (esterification kettle), a pre-polycondensation process (pre-polycondensation reactor) and a final polycondensation process (final polycondensation reactor). Although this reaction process can realize the rapid production of PBT polyester materials, the experimental conditions cannot be accurately controlled during the reaction process, resulting in large differences in the melt viscosity of different batches of PBT. When it is used in the preparation process of PBT fibers, it is easy to cause breakage due to unstable melt viscosity. Summary of the invention
[0004] In view of the technical problem of high fiber breakage rate caused by unstable melt viscosity in the PBT fiber-forming process in the above prior art, the present application discloses a PBT fiber with controllable melt viscosity and low breakage rate and a preparation method thereof, which obtains a polyester material with stable and controllable melt viscosity by changing the industrial production process of PBT, refining and accurately producing process parameters, and then directly produces PBT fiber through spinning technology. This method can effectively reduce the breakage phenomenon caused by unstable melt viscosity in the fiber manufacturing process and reduce product loss.
[0005] To achieve the above object, the present invention provides a method for preparing PBT fiber with stable melt viscosity and low breakage rate, which specifically comprises the following steps:
[0006] S1, stepwise esterification: terephthalic acid, 1,4-butanediol and an esterification catalyst are mixed in a certain molar ratio, and the mixture is added into at least two esterification kettles respectively for esterification reaction to obtain a PBT ester;
[0007] S2, viscosity increasing: mixing the PBT esters obtained from multiple esterification kettles, and then performing viscosity increasing;
[0008] S3, pre-polycondensation: pre-polycondensation of the thickened PBT ester to obtain a PBT prepolymer;
[0009] S4, secondary viscosity enhancement: subjecting the PBT prepolymer to secondary viscosity enhancement;
[0010] S5, final polycondensation: subjecting the PBT prepolymer after secondary viscosity enhancement to final polycondensation reaction, i.e., obtaining a PBT melt;
[0011] S6, fiber forming: after the PBT melt is subjected to spinning, drawing, curling, cutting, relaxation and heat setting, the PBT fiber with stable melt viscosity and low breakage rate is prepared.
[0012] Furthermore, the volume of the esterification kettle is 30-45 cubic meters, and the total amount of material added does not exceed 70%.
[0013] Furthermore, the esterification catalyst is selected from at least one of germanium oxide, antimony trioxide, tetrabutyl titanate, tetraisopropyl titanate, and tetra-tert-butyl titanate.
[0014] Furthermore, in step S1, the molar ratio of terephthalic acid to 1,4-butanediol is 1:1.1-1.4, and the molar ratio of terephthalic acid to esterification catalyst is 1:0.001-0.1.
[0015] Furthermore, in step S1, the reaction temperature is 220-225° C., the reaction pressure is 10-30 kPa, the reaction time is 0.5-2 h, the esterification rate is controlled to be 80-95% during the stepwise esterification, and the viscosity of the obtained PBT ester is 0.01-0.1 dL / g.
[0016] Furthermore, in step S2, the reaction temperature is 225-230° C., the reaction pressure is 30-50 kPa, the reaction time is 0.1-2 h, the esterification rate is controlled to be 90-99%, and the viscosity of the obtained PBT ester is 0.1-0.3 dL / g.
[0017] Furthermore, in step S3, the reaction temperature of the pre-polycondensation is 230-233° C., the vacuum degree is 30-100 kPa, the pre-condensation time is 0.1-2 h, and the viscosity of the obtained PBT prepolymer is 0.3-0.5 dL / g.
[0018] Furthermore, in step S4, the viscosity-increasing reaction temperature is fixed at 233-235° C., the vacuum degree is 200-8000 Pa, the reaction time is 1-2 h, and the viscosity of the PBT prepolymer after the secondary viscosity-increasing is 0.5-1 dL / g.
[0019] Furthermore, in step S5, the secondary viscosity-increasing reaction temperature is 235-240° C., the vacuum degree is 1-200 Pa, the final polycondensation time is 0.1-2 h, and the viscosity of the PBT obtained after the final polycondensation is 1-2 dL / g.
[0020] Furthermore, in step S6, the temperature is fixed at 240-245° C., and the melt viscosity is stabilized during the PBT fiber forming process, and the breakage rate does not exceed 4%.
[0021] Furthermore, in step S1, the viscosity of the obtained PBT ester is 0.09-0.10 dL / g;
[0022] In the step S2, the viscosity of the PBT ester after thickening is 0.25-0.30 dL / g.
[0023] Furthermore, in the step S3, the viscosity of the PBT obtained during the pre-polycondensation is 0.4 to 0.45 dL / g;
[0024] In the step S4, the viscosity of the PBT prepolymer after the secondary viscosity increase is 0.95-1 dL / g.
[0025] Furthermore, the step S5 produces PBT products with different viscosities, and the viscosity fluctuation is ±0.003 dL / g.
[0026] Beneficial effects:
[0027] By accurately and subdividing the PBT production process, the melt viscosity of products at different production stages can be stabilized, thereby reducing the breakage rate in the PBT fiber manufacturing process and optimizing the fiber-forming process. The preparation method of the present invention can improve the stability of products at different production stages, thereby achieving accurate preparation of PBT with different melt viscosities, optimizing the fiber-forming process, reducing product losses, and improving fiber quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a schematic diagram of the process flow of the present invention. DETAILED DESCRIPTION
[0029] The present invention is further described below in conjunction with the accompanying drawings and embodiments.
[0030] Embodiment 1 (optimal process)
[0031] (1) Stepwise esterification: Terephthalic acid, 1,4-butanediol and esterification catalyst were added to the first esterification kettle and the second esterification kettle at a molar ratio of 1:1.2:0.002. The heat transfer oil temperature was set to 225°C, the esterification pressure was set to 30 kPa, the esterification time was 1 hour, and the esterification reaction was completed. The esterification rate of PBT obtained under this process was 95%, and the viscosity was 0.092 dL / g.
[0032] (2) Viscosity increase: The PBT esterified product obtained by step-by-step esterification was transferred to the second esterification kettle, the heat transfer oil was set to 230°C, the esterification pressure was set to 50 kPa, the esterification time was 1 hour, and the co-esterification was completed. The esterification rate of PBT obtained under this process was 99%, and the viscosity was 0.295 dL / g.
[0033] (3) Pre-condensation: The PBT esterified product after co-esterification was transferred to the first polycondensation kettle, the heat transfer oil was set to 233°C, the vacuum degree was 30 kPa, and the pre-condensation time was 1 hour. The viscosity of the PBT prepolymer obtained under this process was 0.451 dL / g.
[0034] (4) Secondary viscosity increase: PBT prepolymer was transferred to the second polycondensation reactor, the heat transfer oil was set to 235°C, the vacuum degree was 200 Pa, and the secondary precondensation time was 0.5 h. The viscosity of PBT obtained under this process was 0.983 dL / g.
[0035] (5) Final polycondensation: PBT with stable viscosity was transferred to the final polycondensation kettle, the heat transfer oil was set at 240°C, the vacuum degree was 10Pa, and the final polycondensation time was 2h. The viscosity of PBT obtained by this process was 1.972dL / g.
[0036] (6) Fibering: The PBT melt with stable melt viscosity is transported to the spinneret assembly, and the PBT fibers are obtained through drawing, curling, cutting, relaxation and heat setting. The PBT fiber breakage rate obtained by this process is 1.3%.
[0037] Example 2
[0038] (1) Stepwise esterification: terephthalic acid, 1,4-butanediol and esterification catalyst were added to the first esterification kettle or the second esterification kettle at a molar ratio of 1:1.2:0.002, the heat transfer oil temperature was set to 225°C, the esterification pressure was set to 30 kPa, the esterification time was 1 hour, and the esterification reaction was completed. The esterification rate of PBT obtained under this process was 95%, and the viscosity was 0.090 dL / g.
[0039] (2) Viscosity increase: The PBT esterified product obtained by step-by-step esterification was transferred to the second esterification kettle, the heat transfer oil was set to 230°C, the esterification pressure was set to 50 kPa, the esterification time was 1 hour, and the co-esterification was completed. The esterification rate of PBT obtained under this process was 99%, and the viscosity was 0.296 dL / g.
[0040] (3) Pre-condensation: The PBT esterified product after co-esterification was transferred to the first polycondensation kettle, the heat transfer oil was set to 233°C, the vacuum degree was 30 kPa, and the pre-condensation time was 1 hour. The viscosity of the PBT prepolymer obtained under this process was 0.453 dL / g.
[0041] (4) Secondary viscosity increase: PBT prepolymer was transferred to the second polycondensation reactor, the heat transfer oil was set to 235°C, the vacuum degree was 200 Pa, and the secondary precondensation time was 0.5 h. The viscosity of PBT obtained under this process was 0.983 dL / g.
[0042] (5) Final polycondensation: PBT with stable viscosity was transferred to the final polycondensation kettle, the heat transfer oil was set at 240°C, the vacuum degree was 10Pa, and the final polycondensation time was 2h. The viscosity of PBT obtained by this process was 1.975dL / g.
[0043] (6) Fibering: The PBT melt with stable melt viscosity is transported to the spinneret assembly, and the PBT fibers are obtained through drawing, curling, cutting, relaxation and heat setting. The PBT fiber breakage rate obtained by this process is 1.2%.
[0044] Comparative Example 1 (the reaction temperature is not within the scope of the claims for comparison, the temperature is low, the viscosity is small, and the breakage rate is high)
[0045] (1) Esterification: A certain proportion of terephthalic acid, 1,4-butanediol and an esterification catalyst are added to the first esterification kettle or the second esterification kettle, the heat transfer oil temperature is set to 215°C, the esterification pressure is set to 30 kPa, the esterification time is 3 hours, and the esterification reaction is completed. The esterification rate of PBT obtained under this process is 62% and the viscosity is 0.015 dL / g.
[0046] (2) Co-esterification: The PBT esterified product obtained by step-by-step esterification was transferred to the second esterification kettle, the heat transfer oil was set to 220°C, the esterification pressure was set to 50 kPa, the esterification time was 3 hours, and the co-esterification was completed. The esterification rate of PBT obtained under this process was 77%, and the viscosity was 0.028 dL / g.
[0047] (3) Pre-condensation: The PBT esterified product after co-esterification was transferred to the first polycondensation kettle, the heat transfer oil was set to 225°C, the vacuum degree was 100 kPa, and the pre-condensation time was 2 hours. The viscosity of the PBT prepolymer obtained under this process was 0.134 dL / g.
[0048] (4) Secondary pre-condensation: PBT prepolymer was transferred to the second polycondensation reactor, the heat transfer oil was set to 230°C, the vacuum degree was 500 Pa, and the secondary pre-condensation time was 2 hours. The viscosity of PBT obtained under this process was 0.329 dL / g.
[0049] (5) Final polycondensation: PBT with stable viscosity was transferred to the final polycondensation kettle, the heat transfer oil was set to 235°C, the vacuum degree was 200Pa, and the final polycondensation time was 4h. The viscosity of PBT obtained by this process was 0.551dL / g.
[0050] (6) Fibering: The PBT melt is transported to the spinneret assembly, and the PBT fibers are obtained through drawing, curling, cutting, relaxation and heat setting. The PBT fiber breakage rate obtained by this process is 12.6%.
[0051] Comparative Example 2 (PBT three-step production, high breakage rate)
[0052] (1) Esterification: A certain proportion of terephthalic acid, 1,4-butanediol and esterification catalyst were added to a 100 cubic meter esterification kettle. The heat transfer oil temperature was set to 225°C, the esterification pressure was set to 30 kPa, the esterification time was 6 hours, and the esterification reaction was completed. The esterification rate of PBT obtained under this process was 96%, and the viscosity was 0.093 dL / g.
[0053] (2) Pre-condensation: PBT esterification product was transferred to the polycondensation reactor, the pre-condensation temperature was 225-235°C, and the vacuum degree of the system was slowly reduced to about 1000 Pa, and the pre-condensation time was 4 hours. The viscosity of the PBT prepolymer obtained under this process was 0.330 dL / g.
[0054] (3) Final polycondensation: The reaction temperature of the polycondensation kettle is controlled between 235-240°C, and the vacuum degree of the polycondensation kettle is slowly reduced to below 100 Pa. The final polycondensation time is 3 hours. The viscosity of the PBT obtained under this process is 1.794 dL / g.
[0055] (4) Fibering: The PBT melt is transported to the spinneret assembly, and the PBT fibers are obtained through drawing, curling, cutting, relaxation and heat setting. The PBT fiber breakage rate obtained by this process is 12.4%.
[0056] Comparative Example 3 (PBT three-step production, same conditions, unstable viscosity, high breakage rate)
[0057] (1) Esterification: A certain proportion of terephthalic acid, 1,4-butanediol and esterification catalyst were added to a 100 cubic meter esterification kettle. The heat transfer oil temperature was set to 225°C, the esterification pressure was set to 30 kPa, the esterification time was 6 hours, and the esterification reaction was completed. The esterification rate of PBT obtained under this process was 89% and the viscosity was 0.025 dL / g.
[0058] (2) Pre-condensation: PBT esterification product was transferred to the polycondensation reactor, the pre-condensation temperature was 225-235°C, and the vacuum degree of the system was slowly reduced to about 1000 Pa, and the pre-condensation time was 4 hours. The viscosity of the PBT prepolymer obtained under this process was 0.293 dL / g.
[0059] (3) Final polycondensation: The reaction temperature of the polycondensation kettle is controlled between 235-240°C, and the vacuum degree of the polycondensation kettle is slowly reduced to below 100 Pa. The final polycondensation time is 3 hours. The viscosity of the PBT obtained under this process is 1.497 dL / g.
[0060] (4) Fibering: The PBT melt is transported to the spinneret assembly, and the PBT fibers are obtained through drawing, curling, cutting, relaxation and heat setting. The PBT fiber breakage rate obtained by this process is 10.5%.
[0061] Table 1 PBT fiber forming process parameters
[0062]
[0063]
[0064] Result analysis:
[0065] As can be seen from Table 1, compared with Comparative Example 1, Examples 1 and 2 can make the melt viscosity of PBT in different processes tend to be stable by accurately subdividing the production process of PBT and fixing the process parameters, which is beneficial to the material stability of the same brand of PBT and the serial production of different brands of PBT, and effectively reduces the fiber formation rate in the preparation process of PBT fiber; Compared with Comparative Examples 2-3, the process conditions defined in the present invention can significantly reduce the breakage rate in the fiber formation process of PBT, reduce energy consumption, and optimize production.
[0066] Although the above describes the specific implementation mode of the present invention in conjunction with the accompanying drawings, it is not intended to limit the scope of protection of the present invention. Those skilled in the art should understand that various modifications or variations that can be made by those skilled in the art on the basis of the technical solution of the present invention without creative work are still within the scope of protection of the present invention.
Claims
1. A method for preparing PBT fiber with stable melt viscosity and low breakage rate, characterized in that: The steps include: S1. Stepwise esterification: terephthalic acid, 1,4-butanediol and an esterification catalyst are mixed in a certain molar ratio, and the mixture is respectively conveyed to at least two esterification kettles for esterification reaction to obtain PBT esterification product; the molar ratio of terephthalic acid to 1,4-butanediol is 1:1.1-1.4, and the molar ratio of terephthalic acid to the ester exchange catalyst is 1:0.001-0.1; the reaction temperature is fixed at 220-225°C, the system pressure is fixed at 10-30 kPa, the reaction time is 0.5-2h, and the esterification rate is controlled to be 80-95% during the stepwise esterification; S2, viscosity increasing: the prepared PBT esters are mixed and then viscosity increasing is performed; the reaction temperature is fixed at 225-230°C, the system pressure is fixed at 30-50 kPa, the reaction time is 0.1-2 hours, the esterification rate is controlled to be 90-99% during co-esterification, and the viscosity of the obtained PBT prepolymer is 0.1-0.3 dL / g; S3, pre-condensation: pre-condensation of the thickened PBT ester to obtain a PBT prepolymer; the reaction temperature of the pre-condensation is fixed at 230-233°C, the vacuum degree is 30-100 kPa, and the pre-condensation time is 0.1-2h; the viscosity of the PBT obtained during the pre-condensation is 0.3-0.5 dL / g; S4, secondary viscosity increase: subjecting the PBT prepolymer to secondary viscosity increase; the secondary viscosity increase reaction temperature is 233-235° C., the vacuum degree is 200-8000 Pa, the reaction time is 1-2 hours, and the viscosity of the PBT prepolymer after the secondary viscosity increase is 0.5-1 dL / g; S5, final polycondensation: subjecting the PBT prepolymer after secondary viscosity enhancement to final polycondensation reaction, i.e., obtaining PBT melt; the reaction temperature is fixed at 235-240°C, the vacuum degree is 1-200Pa, the final polycondensation time is 0.1-2h, and the viscosity of the PBT obtained after the final polycondensation is 1-2dL / g; S6, fiber forming: the PBT melt is subjected to spinning, drawing, curling, cutting, relaxation and heat setting to prepare the PBT fiber with stable melt viscosity and low breakage rate; The processing capacity of a single esterification kettle is 30-45L, and the total amount of material added does not exceed 70%.
2. The preparation method according to claim 1, characterized in that: In the step S6, the reaction temperature is 240-245° C., and the melt viscosity is stable. During the PBT fiber forming process, the breakage rate does not exceed 4%.
3. The preparation method according to claim 1, characterized in that: The esterification catalyst is selected from at least one of germanium oxide, antimony trioxide, tetrabutyl titanate, tetraisopropyl titanate, and tetra-tert-butyl titanate.
4. The preparation method according to claim 1, characterized in that: In the step S1, the viscosity of the PBT esterified product after the stepwise esterification is completed is 0.09-0.10 dL / g; in the step S2, the viscosity of the PBT esterified product after thickening is 0.25-0.30 dL / g; in the step S3, the viscosity of the PBT prepolymer is 0.40-0.45 dL / g; in the step S4, the viscosity of the PBT prepolymer after secondary thickening is 0.95-1.00 dL / g.
Citation Information
Patent Citations
Method for preparing PBT polyester fibers by melt direct spinning
CN111088547A